2023
DOI: 10.1038/s41531-023-00549-2
|View full text |Cite
|
Sign up to set email alerts
|

Does Black vs. White race affect practitioners’ appraisal of Parkinson’s disease?

Abstract: Black patients are diagnosed with Parkinson’s disease (PD) at half the rate as White patients. The reasons for this large disparity are unknown. Here, we review evidence that practitioner bias may contribute. A key sign of PD is hypomimia or decreased facial expressivity. However, practitioner bias surrounding facial expressivity in Black people versus White people may lead practitioners to appraise Black patients with hypomimia as having higher levels of facial expressivity. Furthermore, practitioner bias may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Indeed, it has been suggested that there may be a practitioner bias that leads to reduced diagnoses of PD among Black individuals. 35 As such, it is possible that race discrepancies in PD prevalence may re ect actual differences in the frequency of PD cases or a bias in diagnosis due to other, systemic factors, or both. Indeed, we recognise that our results may be mediated by demographic, environmental, social and/or systematic factors that could leave certain groups more vulnerable to PD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been suggested that there may be a practitioner bias that leads to reduced diagnoses of PD among Black individuals. 35 As such, it is possible that race discrepancies in PD prevalence may re ect actual differences in the frequency of PD cases or a bias in diagnosis due to other, systemic factors, or both. Indeed, we recognise that our results may be mediated by demographic, environmental, social and/or systematic factors that could leave certain groups more vulnerable to PD risk.…”
Section: Discussionmentioning
confidence: 99%
“…It is also established that PD diagnoses are often delayed in Black adults and occur at a greater disease severity [ 52–54 ]. There are multiple proposed contributors to this, including healthcare access/disparities [ 52–54, 56 ], distrust of the medical system [ 52, 53 ], more comorbidities in Black adults [ 54 ], earlier age of mortality in Black adults [ 53 ], perceptions of aging (i.e., viewing parkinsonism as part of normal aging) [ 52, 53, 57 ], clinician biases (in diagnosis, treatment) [ 52, 53 ], and clinician biases related to assessing hypomimia/facial expression [ 58 ]. However, there is also community-based research suggesting that parkinsonian signs may be less frequent in older Black adults compared to older White adults [ 59 ].…”
Section: The Intersection Of Race and Core Features Of Dlbmentioning
confidence: 99%